Sinopsis en Idioma Inglés - Reflexión Política, Revistas (Reflexión Política, 1999)
Resumen The Role of The UN in Countries Where There is Internal Conflict in a Post Cold War Context By Ana María Montoya Durana International participation in internal conflicts in the context of the post cold war era have taken place under humanitarian pretexts and by a series of international actors, for example agencies and forces like the United Nations, multilateral regional organisations, international NGOs and in some cases states as individual actors. This phenomenon has been described by some authors as New Interventionism.